Manajemen Kelas dan Problematika Kepribadian Guru - Achmad Ridlowi (Transformasi : Jurnal Studi Agama Islam, 2022)
Class management is one of the skills that every teacher must have. This is because class conduciveness will only be achieved by applying good classroom management. The class condition itself is the most important aspect for the implementation of effective, efficient, and enjoyable learning. The research method in this study is a literature review. In this literature review, the researcher not only reads the literature, but also conducts an in-depth and critical evaluation of previous research on a topic. The aim of the researcher is to conduct an in-depth study to explain how classroom management is conducive to learning. The results of the study indicate that the aspects that must be considered and understood by teachers in class management are as follows; 1) Designing the physical classroom environment (seating arrangements, visualization), 2) Creating a positive environment for learning (fair attitude, compassion for students, positive thinking), 3) Being a good communicator (gentle, communicate according to the intellectual level of students , communication in simple language, argue in a good way, and 4) Ability to solve problems.